Glass-like polymers based on benzoxazine derivatives
By introducing the benzooxazine monomer containing disulfide bonds, glass-like polymers of polybenzooxazine derivatives were developed, which solved the problem that existing thermosetting materials could not be recycled and reprocessed, and achieved the self-healing, reforming, reprocessing and recirculation of the materials.
Patent Information
- Application Number
- CN202180020807.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-12
- Filing Date
- 2021-03-04
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-03-04
AI Technical Summary
Existing thermosetting materials such as polybenzoxazine cannot be recycled, reprocessed or removed from metal parts, limiting their use in multiple uses and complex structures.
By introducing disulfide-containing benzooxazine monomers, glass-like polymers of polybenzooxazine derivatives are developed, and the self-healing, reforming, reprocessing and recycling of the material is achieved by using dynamic combined exchange reactions.
The self-healing, reforming, reprocessing and recycling of polybenzoxazine materials has been achieved, and its application potential in multiple uses and complex structures has been enhanced.
Smart Images

Figure CN115335366B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a glass-like polymer (vitrimer) of a benzoxazine derivative, and to a process for preparing the same and the use of the glass-like polymer in various applications. Background Art
[0002] Composites are almost always made from thermoset resins, which are the material of choice for many applications due to their dimensional stability, mechanical properties, and creep / chemical resistance. However, as a result of their permanent molecular structure, they cannot be recycled or reprocessed and end up in landfills.
[0003] The chemical method to deal with this shortcoming is provided as follows: introduce exchangeable chemical bonds, resulting in dynamic crosslinking. Polymer networks containing such exchangeable bonds are also called covalent adaptable networks (CAN) (W. Denissen et al. -Wim Denissen, Johan M. Winne and Filip E. Du Prez, Chem. Sci., 2016, 7, 30-38). CAN can be further divided into two groups-dissociative or associative, depending on its exchange mechanism. In the first group, the chemical bond is first broken and then formed again at another position. Diels Alder reaction is the most common mechanism of dissociative CAN. In the second group, the polymer network does not depolymerize when heated, but is characterized by a fixed crosslinking density. Covalent bonds are only broken when new covalent bonds are formed, making these networks both permanent and dynamic. The first reported associative CAN (2005) is based on a light-mediated reaction carried out by using, for example, allyl sulfide. Later, a similar exchange mechanism was introduced by using an alternative free radical generator with trithiocarbonate. In 2011, Leibler et al. (D. Montarnal, M. Capelot, F. Tournilhac and L. Leibler, Science, 2011, 334, 965-968) expanded the field of combined CAN by adding a suitable transesterification catalyst to a network based on epoxy / acid or epoxy / anhydride polyesters to obtain a permanent polyester / polyol network that shows a gradual decrease in viscosity upon heating. Such unique features of vitreous silica have never been observed in organic polymer materials. Therefore, the authors introduced the name of vitrimer for these materials.
[0004] Based on the seminal work of Leibler et al. (mentioned earlier), this new class of materials can be defined by a number of criteria. First, glass-like polymers consist of covalently bonded chains forming an organic network, insoluble in solvents. This network is further able to change its topology via associative exchange reactions, and is thermally triggered, resulting in thermal ductility of the network. At higher temperatures, the viscosity of glass-like polymers is essentially controlled by chemical exchange reactions, resulting in a decrease in thermal viscosity that follows the Arrhenius rule.
[0005] Based on the properties of dynamic associative exchange reactions (especially sulfur-sulfur connections), various glass-like polymer materials have been developed. Recently, Pepels et al. (M. Pepels, I. Filot, B. Klumperman and H. Goossens, Polym. Chem., 2013, 4, 4955-4965) reported a dynamic network based on thiol-disulfide exchange reactions, which showed properties similar to glass-like polymers.
[0006] In 2014, Martin et al. (R. Martin, A. Rekondo, A. Ruiz de Luzuriaga, G. Cabanero, HJ Grande and I. Odriozola, J. Mater. Chem. A, 2014, 2, 5710-5715) demonstrated reprocessable elastomers using aromatic disulfide metathesis in poly (urea-urethane) networks. These networks show quantitative self-healing at room temperature, which is due to both dynamic hydrogen bond formation and network reorganization. In addition, Rekondo et al. (A. Rekondo, R. Martin, ARd Luzuriaga, G. Cabanero, HJ Grande and I. Odriozola, Mater. Horiz., 2016, 3, 241-247) developed fiber-reinforced polymer composites made of epoxy resins and dynamic disulfide bonds, which can be reprocessed and recycled. While 3D-printed thermosets are desirable, they are inherently non-recyclable due to their permanently cross-linked networks, whereas Qi et al. developed the first example of a recyclable 3D-printable epoxy glass-like polymer (Qian Shi, Kai Yu, Xiao Kuang, Xiaoming Mu, Conner K. Dunn, Martin L. Dunn, Tiejun Wang and H. Jerry Qi, Mater Horiz., 2017, 4, 598-607).
[0007] Polybenzoxazines are a new class of thermosets that have excellent mechanical and thermal properties, as well as strong irreversible adhesion to metal substrates. Like many other thermosets, they cannot be reshaped, reprocessed, recycled, or disassembled from metal parts. Some examples have been reported that show reasonable levels of healing (L. Zhang, Z. Zhao, Z. Dai, L. Xu, F. Fu, T. Endo, X. Liu, ACS Macro. Lett. 2019, 8, 5, 506-511, and Arslan M., Kiskan B., Y. Yagci, Sci. Rep. 2017, 7, 5207). However, polybenzoxazines remain a class of high-performance materials that have neither demonstrated glass-like polymer capabilities nor reversible adhesion to metal substrates. Summary of the invention
[0008] The present invention provides a solution to at least one of the above-mentioned disadvantages of the prior art. For this purpose, the present invention relates to a benzoxazine monomer containing disulfide (disulfide bond, disulfide, disulfide) of formula (I)
[0009]
[0010] Where R is:
[0011]
[0012] Wherein, in formula (II), X and X' are independently substituted or unsubstituted aliphatic C 1 -C 20 an alkyl group, the alkyl group optionally containing heteroatoms; and / or a substituted or unsubstituted aliphatic C 2 -C 20 an alkenyl group, the alkenyl group optionally containing heteroatoms; and / or at least one substituted or unsubstituted C 6 -C 20 Aryl group; and / or at least one substituted or unsubstituted C 6 -C 20 heteroaryl group; and / or at least one substituted or unsubstituted C 6 -C 20 heterocyclic group, and / or at least one substituted or unsubstituted C 3 -C 8 a cycloalkyl group, wherein the heteroatom is selected from N, O, and S,
[0013] And where R 1 , R 2 , R 3 , R 4 The combination of substituents is selected from the following combinations:
[0014] R 1 = R 2 = R 3 = R 4 = H,
[0015] R 1 = OCH 3 ,R 2 = R 3 = R 4 = H,
[0016] R 1 = OCH 3 ,R 2 = R 4 = R 3 = C 1 -C 15 alkyl group
[0017] R 1 = OCH 3 ,R 2 = R 4 = H,R 3 = CHO,
[0018] R 1 = OCH 3 ,R 2 = R 4 = H,R 3 = (CH 2 ) n:1-15 COOH,
[0019] R 1 = OCH 3 ,R 2 = R 4 = H,R 3 = (CH 2 ) n:1-15 CH = CH 2 ,
[0020] R 1 = OCH 3 ,R 2 = R 4 = H,R 3 = CH = CHCH 3 ,
[0021] R 1 = R 2 = R 4 = H,R 3 = (CH 2 ) n:1-15 COOH,
[0022] R 1 =R 2 =R 4 =H, R 3 =CH=CHCOOH,
[0023] R 1 =OCH 3 , R 2 =R 4 =H, R 3 =CH=CHCOOH,
[0024] R 1 =OCH 3 , R 2 =R 4 =H, R 3 =(CH 2 ) n:1-15 COOH,
[0025] R 1 , R 2 , R 3 , R 4 At least one of them is C 1 -C 15 aliphatic alkyl groups, the remainder being H,
[0026] R 1 =R 3 =R 4 =H, and
[0027] and / or
[0028] R 3 =R 4 =H, R 1 =COOH
[0029] and / or
[0030] R 1 =H, R 2 =OH, R 3 =H, and and / or
[0031] R 1 =H, R 3 =OH, R 4 =H, and and / or
[0032] R 1 =CH3 , R 2 =OH, R 3 =H,
[0033] and / or
[0034] R 3 =R 4 =H, R 1 =OH, and
[0035] and / or
[0036] R 2 =R 3 =R 4 =H, and R 1 =(CH 2 ) n:1-15 CH=CH 2 ,
[0037] R 1 =R 3 =R 4 =H, and R 2 =(CH 2 ) n:1-15 CH=CH 2 ,
[0038] R 1 =R 2 =R 4 =H, and R 3 =(CH 2 ) n:1-15 CH=CH 2 ,
[0039] R 1 =R 3 =R 4 =H, and as well as
[0040] R 1 =R 2 =R 4 =H, and
[0041] or a mixture thereof
[0042] Where R 1 '、R 2 '、R 3 '、R 4 'Substituent combinations such as for R 1 , R 2 , R3 , R 4 The combinations of substituents are defined by, and are independent of, each other.
[0043] Preferably, the compound N,N'-(disulfanediylbis(methylene))bis(6-(2H-benzo[e][1,3]oxazol-3(4H)-yl)hexan-1-amine is excluded. The disulfide-containing benzoxazine monomer of the present invention is advantageously suitable for obtaining a glass-like polymer of a polybenzoxazine derivative by polymerization involving benzoxazine ring opening and self-polymerization under heating to obtain the glass-like polymer of the polybenzoxazine derivative. Due to the specific monomer starting product, the glass-like polymer of the present invention exhibits self-healing, reshaping, reprocessing, and recycling properties. In the remainder of this document, the glass-like polymer of benzoxazine will always refer to the polymerized form of the benzoxazine monomer.
[0044] The glass-like polymer properties of polybenzoxazine derivatives are closely related to the properties of benzoxazine monomers.
[0045] As can be seen from formula (I), the monomer includes a benzoxazine ring portion, which allows the monomer to crosslink upon heating and facilitates reprocessing due to the formation of reversible H bonds (glass-like polymers) once crosslinked. The optional presence of an alkyl group on the benzoxazine ring portion can enhance the processability of the monomer, which also leads to the reprocessability of the glass-like polymers of the benzoxazine derivatives. The presence of a portion composed of a diamine containing a disulfide bond is critical to the formation of a dynamic and reversible network of the glass-like polymers of the benzoxazine derivatives, allowing material recycling, reshaping, and reprocessing. Therefore, the key features of the monomers of the present invention rely on the benzoxazine-containing portion and the disulfide bonds. The Tg of such polybenzoxazines can be from -50°C to 300°C.
[0046] Advantageously, in formula (II), X and X' may independently be: a substituted or unsubstituted aliphatic C 1 -C 15 Alkyl group, preferably C 1 -C 8 Alkyl groups, optionally containing heteroatoms N, O, S; and / or substituted or unsubstituted aliphatic C 2 -C 15 Alkenyl group, preferably C 2 -C 8 The alkenyl group may contain heteroatoms N, S, O; and / or at least one substituted or unsubstituted C 6 -C 15 Aryl group; and / or at least one substituted or unsubstituted C 6 -C 15heteroaryl group; and / or at least one substituted or unsubstituted C 6 -C 15 Heterocyclic group, and / or at least one C 3 -C 6 Cycloalkyl groups.
[0047] More preferably, R can be selected from the following moieties:
[0048]
[0049] and and
[0050] Independently, R 1 , R 2 , R 3 , R 4 Substituents and R 1 '、R 2 '、R 3 '、R 4 'Substituent combinations such as for R 1 , R 2 , R 3 , R 4 The combination of substituents is defined by and independently thereof, which can be selected from the following combinations:
[0051] R 1 =OCH 3 , R 2 =R 4 =R 5 =H, R 3 =C 1 -C 15 The alkyl group,
[0052] R 1 =OCH 3 , R 2 =R 4 =H, R 3 =(CH 2 ) n:1-15 COOH,
[0053] R 1 =OCH 3 , R 2 =R 4 =H, R 3 =(CH 2 ) n:1-15 CH=CH 2 ,
[0054] R 1 =R 2 =R 4 =H, R3 =(CH 2 ) n:1-15 COOH,
[0055] R 1 =OCH 3 , R 2 =R 4 =H, R 3 =(CH 2 ) n:1-15 COOH,
[0056] R 1 , R 2 , R 3 , and R 4 At least one of them is C 1 -C 15 aliphatic alkyl groups, the rest are H, R 1 =R 3 =R 4 =H, and
[0057] and / or
[0058] R 3 =R 4 =H, R 1 =COOH
[0059] and / or
[0060] R 1 =H, R 2 =OH, R 3 =H, and and / or
[0061] R 1 =H, R 3 =OH, R 4 =H, and and / or
[0062] R 1 =CH 3 , R 2 =OH, R 3 =H,
[0063] and / or
[0064] R 3 =R 4 =H, R 1 =OH, and
[0065] and / or
[0066] R 2 =R 3 =R 4 =H, and R 1 =(CH 2 ) n:1-15 CH=CH 2 ,
[0067] R 1 =R 3 =R 4 =H, and R 2 =(CH 2 ) n:1-15 CH=CH 2 ,
[0068] R 1 =R 2 =R 4 =H, and R 3 =(CH 2 ) n:1-15 CH=CH 2 ,
[0069] R 1 =R 3 =R 4 =H, and and
[0070] R 1 =R 2 =R 4 =H, and
[0071] or a mixture thereof.
[0072] These compounds are more preferred because the presence of a long chain alkane on the benzoxazine ring portion, which optionally includes an unsaturated bond such as C=C, a methylene chain, and / or a substituent with a cyclic hydrocarbon containing N or O in the ring, improves the processability of the monomer, which also leads to an increase in the reprocessability of the glass-like polymer of the benzoxazine derivative from the viewpoint of a lower reprocessing temperature. Compared with unsubstituted monomers or slightly substituted compounds (such as those with CH=CHCOOH, -OCH 3Compared with unsubstituted monomers or slightly substituted compounds, the melt viscosity of such monomers is reduced. Compared with unsubstituted monomers or slightly substituted compounds, the glass-like polymers obtained using such monomers can exhibit lower Tg and reprocessing temperatures, for example, exhibiting the following Tg range values: -50°C to 250°C, preferably 0°C to 200°C, more preferably 20°C to 100°C, and the reprocessing temperature is higher than the Tg range values.
[0073] Such compounds may be most preferred: wherein R 1 , R 2 , R 3 , R 4 Substituents and R 1 '、R 2 '、R 3 '、R 4 'Substituent combination with a methylene chain (CH 2 ) n , wherein the value of n may be in the range of 2 to 15, especially 4 to 15, and C 2 -C 15 , especially C 4 -C 15 The alkyl groups of the present invention may optionally include unsaturated bonds, such as C=C. The lowest Tg and reprocessing temperature of glass-like polymers are obtained, and (as described above, compared with unsubstituted monomers or slightly substituted compounds), such monomers have the lowest melt viscosity. For example, the Tg range may be -50°C to 150°C, and the reprocessing temperature is higher than the Tg range.
[0074] In some alternative embodiments, the -S of the phenyl moiety in compound (A) may be in the ortho or meta position, however less preferred.
[0075] The present invention also relates to a process for synthesizing a disulfide-containing benzoxazine monomer of formula (I), the process comprising the following steps consisting of:
[0076] a) providing a mixture comprising:
[0077] -Formula (III): H 2 NR-NH 2 An amino disulfide compound wherein R is as defined for the monomer of formula (I),
[0078] - aldehyde derivatives; and
[0079] - Phenol derivatives of formula (IV) and (V)
[0080]
[0081] Where R1 , R 2 , R 3 , R 4 and R 1 '、R 2 '、R 3 '、R 4 The combination of substituents is independent and as defined above, and wherein R 5 and R 5 ' is independently H.
[0082] b) stirring the mixture at a temperature of 50° C. to 130° C. for 1 to 48 hours to obtain the monomer of formula (I);
[0083] The stoichiometric ratios of aminodisulfide compound: aldehyde derivative: phenol derivative are 1:4:x 1 +x 2 , where x 1 +x 2 =2, and 0 <x 1 ;x 2 <2.
[0084] The disulfide-containing benzoxazine monomer of the present invention is advantageously suitable for obtaining a glass-like polymer of a polybenzoxazine derivative by polymerization involving ring-opening and self-polymerization of benzoxazine under heating.
[0085] The applicant has shown that specific starting reactants provide disulfide-containing benzoxazine monomers, which in turn provide glass-like polymers containing polybenzoxazine derivatives of polymerized benzoxazine after polymerization. Thus, the benzoxazine ring obtained from the reaction of specific aminodisulfide compounds (Formula (III)) and phenolic derivatives (Formulas (IV) and (V)) allows the material to be crosslinked (processed) upon heating, facilitating reprocessing due to the reversible H-bonds formed once crosslinked and dynamic disulfide bonds. In addition, the benzoxazine ring portion provides thermosetting properties such as high temperature and combustion performance, high strength, thermal stability, low water absorption, chemical resistance, low melt viscosity, and near zero shrinkage.
[0086] Finally, disulfide and hydrogen bonds are critical for the formation of glass-like polymers of polybenzoxazine derivatives with dynamic networks that allow for material recycling, reformulation, and reprocessing.
[0087] Furthermore, disulfide bonds are also critical for allowing adhesion of glass-like polymers on substrates, especially metallic substrates.
[0088] Preferably, the aldehyde derivative is selected from formaldehyde, paraformaldehyde, or a mixture thereof.
[0089] Preferably, the process is carried out with bio-based reactants, since one of the main components may be cardanol or its derivatives, eugenol, and phloric acid, or a mixture thereof.
[0090] Most preferably, the monomer synthesis may be solvent-free, although solvents may be added for dissolving the starting reactants. The process involves a one-step synthesis, which is one of the advantages of the present invention.
[0091] Advantageously, the synthesis may not generally require any monomer purification to practice the invention. However, if desired, monomer purification may be performed by any known technique (vacuum, distillation, etc.). The reaction mixture may be stirred using a classical mechanical stirrer, or any non-limiting means.
[0092] This process requires a specific choice of the stoichiometry of the starting reactants. The stoichiometry of the phenolic derivative of formula (IV) is x 1 , and the stoichiometry of the phenolic derivative of formula (V) is x 2 , where x 1 +x 2 =2 and 0 <x 1 ;x 2 <2.
[0093] The molar ratio of each phenol derivative is not limited, one of the reasons is that R 1 , R 2 , R 3 , R 4 , R 5 and R 1 '、R 2 '、R 3 '、R 4 The combinations of R ' and R 5 ' are independently the same.
[0094] Advantageously, the phenolic derivative is independently at least one of the phenolic derivatives selected from the group consisting of phenol, guaiacol, wood tar alcohol, vanillin, vanillic acid, eugenol, isoeugenol, phlorothiol, coumaric acid, ferulic acid, dihydroferulic acid, cresol (o-, m-, and / or p-), a moiety comprising at least one of 2 to 15 carbon atoms (e.g. C 2 , C 3 , C 4 , C 5 , C 6 , C 7 , C 8 , C 9 , C 10 , C 11 , C 12 , C 13 , C 14 and / or C 15) substituted phenols (o-, m-, and / or p-), cardanol derivatives, anacardic acid, cardanol, 2-methylcardanol, urushiol, o-allylphenol, m-allylphenol, p-allylphenol, 3-(furan-2-yl)phenol, and 1-(4-hydroxyphenyl)-1H-pyrrole-2,5-dione, or a mixture thereof.
[0095] The process can be carried out by any known means known to those skilled in the art, using appropriate utensils.
[0096] The synthesis of the monomers is carried out under heating, the temperature of the mixture preferably being between 60° C. and 130° C., depending on the nature of the reactants, i.e. the melting temperature of the reaction medium, and / or also on the nature of the solvent. It is preferred to select a temperature value below the boiling point of the reactants and / or the solvent.
[0097] The reaction duration is 1 h to 48 h, depending on the kinetics of the reaction and whether a solvent is present. Preferably, the reaction duration may be 1 h to 24 h, more preferably 5 h to 24 h, most preferably 7 h to 20 h.
[0098] In some embodiments, the synthesis of the disulfide-containing benzoxazine monomer is carried out without using any solvent, the reaction temperature may be in the range of 60° C. to 120° C., and the reaction duration may preferably be 1 h to 24 h, more preferably 7 h to 20 h.
[0099] In some embodiments, where the synthesis of the disulfide-containing benzoxazine monomer is carried out using a solvent, the reaction temperature may be in the numerical range of 70° C. to 130° C., and the reaction duration may preferably be 5 h to 24 h, more preferably 7 h to 20 h. Any appropriate solvent may be used to dissolve the starting reactants. The appropriate solvent may be selected from THF, dioxane, chloroform, and toluene, or a mixture thereof. Once the reaction is achieved, the solvent may preferably be evaporated by classical means (e.g., under vacuum).
[0100] The present invention also relates to a process for preparing a glass-like polymer of a polybenzoxazine derivative, the process comprising a step of polymerizing the benzoxazine monomer of the present invention or obtained by the above process, the step being carried out at a temperature in the range of 100° C. to 250° C. for 1 h to 24 h to obtain a glass-like polymer of a polybenzoxazine derivative.
[0101] According to the process for preparing the glass-like polymer of the present invention, the polymerization step is a curing step, allowing the benzoxazine ring to open and react with itself to form a 3D network, in which intermolecular and intramolecular hydrogen bonds between the amino group and the phenolic hydroxyl group are formed (HD Kim, H. Ishida, Macromolecules, 36 (22) (2003) 8320-8329; B. Kiskan, React. Fund. Polym, 129 (2018) 76-88). The duration of polymerization depends on the curing temperature and / or the properties of the benzoxazine monomer. For a given monomer, the polymerization temperature is selected to be higher than the temperature required to synthesize the monomer. In general, the higher the polymerization temperature, the shorter the curing duration. For example, when the polymerization temperature is 250°C, the curing duration may be at least 1 hour, while for a polymerization temperature of 100°C, the curing duration may be no more than 48 hours. Preferably, the curing temperature may be 150 to 200°C, more preferably 170 to 190°C, the latter range providing a curing duration of 1 to 3 hours, preferably 1 to 2.5 hours. The polymerization may be performed by any known heating means such as laser beam and infrared beam.
[0102] Advantageously, the process may be a process for producing / preparing a glass-like polymer of a polybenzoxazine derivative exhibiting at least one of the following properties: self-healing, reforming, reprocessability, recycling, reversible adhesion, thermosetting, and insolubility in solvents, or a mixture thereof.
[0103] Advantageously, the polymerization temperature may be defined as the maximum of the exothermic peak measured by differential scanning calorimetry (DSC).Glass-like polymer materials retain their shape upon cooling.
[0104] When the resulting glass-like polymer is heated again, for example at a temperature of 50°C to 200°C, the disulfide bonds break and reform, allowing the glass-like polymer to be reformed, recycled, or reprocessed. The polybenzoxazine structure relies on hydrogen bonding, which is the core asset that allows the mechanical cohesion of the glass-like polymer.
[0105] The process may also include a post-polymerization step consisting of a heating step, which may preferably be performed at a temperature higher than the temperature of the polymerization heating step.
[0106] The present invention also relates to a glass-like polymer of a polybenzoxazine derivative, which can be obtained by the process described above and exhibits at least one of the following characteristics:
[0107] (i) a Tg value of 0°C to 250°C; and
[0108] (ii) The relaxation temperature is between 0°C and 250°C, above the Tg value.
[0109] Advantageously, the glass-like polymer may also exhibit at least one of the following properties selected from the group consisting of:
[0110] - a relaxation time of 0.1 s to 2 h, preferably 1 s to 1 h, more preferably 1 s to 30 minutes, wherein the relaxation time is defined as the time required for the polymer to relax by 50% at a certain temperature after stress is applied. The glass-like polymer can deform between 0.1% and 100% of its initial size;
[0111] - the activation energy associated with the relaxation time may be from 10 kJ / mol to 300 kJ / mol, preferably from 20 kJ / mol to 200 kJ / mol; and
[0112] - The treatment temperature may be from 50°C to 200°C, preferably from 70°C to 150°C.
[0113] The glass-like polymer according to the present invention also very preferably exhibits the following properties: it behaves as a thermoset and / or exhibits insolubility in solvents such as CHCl 3 , CH 2 Cl 2 , DMF, THF, aromatic solvents such as toluene and / or xylene. The swelling properties were observed to a degree of 0 to 500% of its initial weight.
[0114] It should be emphasized that the presence of a long alkyl chain, a methylene chain, and / or a substituent with a cyclic hydrocarbon containing N or O in the benzoxazine ring portion of the monomer used to synthesize the glass-like polymer can advantageously enhance the reprocessability of the glass-like polymer of the benzoxazine derivative from the viewpoint of processing temperature and viscosity in the melt state, as described above.
[0115] The glass-like polymers of the present invention exhibit self-healing, reforming, reprocessing, recycling, and reversible adhesion properties.
[0116] The glass-like polymer may constitute a layer on a substrate, more preferably an intermediate layer between at least two substrates, such as metals, polymers, glasses, and ceramic materials. The resulting composite material may be prepared by placing at least one disulfide-containing benzoxazine monomer on a substrate, more preferably on two substrates under consideration, followed by curing at a temperature that provides the glass-like polymer without altering the integrity of the substrates. The substrates may be different from each other.
[0117] The metal type substrate is not limited and may be aluminum, iron, steel, or the like.
[0118] The polymer substrate may be polycarbonate, acrylic, polyamide, polyethylene or terephthalate.
[0119] Thus, disulfide-based benzoxazine glass-like polymers can be advantageously used in a variety of non-limiting technological fields, such as electronics, aerospace, defense, and automotive fields.
[0120] The present invention also relates to a process for manufacturing a material comprising at least one substrate coated with a glass-like polymer of the polybenzoxazine derivative of the present invention, wherein the glass-like polymer exhibits at least one of the following properties: self-healing, reshaping, reprocessability, recycling, reversible adhesion properties, thermosetting, and insolubility in solvents, or a mixture thereof, the process comprising the following steps:
[0121] (i) depositing at least one disulfide-containing benzoxazine monomer of formula (I) onto a substrate;
[0122] (ii) polymerizing the benzoxazine monomer of step (i) on the substrate at a temperature ranging from 100° C. to 250° C. for 1 hour to 24 hours.
[0123] The present invention also relates to a composition A comprising:
[0124] a) a benzoxazine derivative of formula (I), and
[0125] b) at least one or more additional compounds of the organic molecular type, which may or may not contain a benzoxazine moiety.
[0126] Preferably, the organic molecule type may be a polymer with or without a benzoxazine moiety.
[0127] The additional compounds may be used to enhance the properties of the monomer or the glass-like polymer (ie, viscosity, mechanical and thermal properties), or both.
[0128] The polymer may be an epoxy resin, a bismaleimide resin, a phenolic resin or a benzoxazine resin, a polyurethane, a polyamide, a polyolefin, a polyester, a rubber. The benzoxazine derivative of formula (I) may be used in a weight ratio of 0.1 to 80% of the final composition.
[0129] The compounds of formula (I) can be used to provide glass-like polymer properties (self-healing, reprocessing, etc.) to the above-mentioned polymers.
[0130] The present invention also relates to a composition B comprising:
[0131] a) a benzoxazine derivative of formula (I), and
[0132] b) Materials selected from fillers, fibers, pigments, dyes, and plasticizers.
[0133] The additional compounds may be used to enhance the properties of the monomer or the glass-like polymer (ie, viscosity, mechanical and thermal properties), or both.
[0134] The additional compound may be: carbon fibers, glass fibers, clay, carbon black, silica, carbon nanotubes, graphene, any known means for thermal or mechanical reinforcement of the composition.
[0135] The present invention also relates to the use of the glass-like polymer according to the present invention as a reversible adhesive, sealant, coating, or encapsulation system for a substrate selected from metal, polymer, glass, and ceramic material. Preferably, the metal and polymer are as defined above.
[0136] The present invention also relates to the use of the glass-like polymer according to the present invention in a 3D printing process or an additive manufacturing process. BRIEF DESCRIPTION OF THE DRAWINGS
[0137] Other features and advantages of the present invention will be readily understood from the following detailed description and accompanying drawings, in which:
[0138] - Figure 1 The synthesis reaction of benzoxazine monomers from cardanol as phenolic derivative is shown;
[0139] - Figure 2 shows a network of glass-like polymers obtained by curing cardanol benzoxazine monomers (schematic form);
[0140] - Figure 3 is the NMR spectrum of cardanol benzoxazine monomer;
[0141] - Figure 4 This is the FTIR spectrum of the cardanol derivative benzoxazine monomer;
[0142] - Figure 5 The DSC curve of cardanol benzoxazine monomer is shown;
[0143] - Figure 6 Rheological diagram of the cardanol derivative benzoxazine monomer showing the evolution of complex viscosity upon heating at 170°C;
[0144] - Figure 7 shows the evolution of the relaxation modulus of the glass-like polymer obtained by curing the cardanol benzoxazine monomer;
[0145] - Figure 8 The evolution of the relaxation time t* as a function of 1000 / T is shown.
[0146] - Fig. 9Schematic illustration of the recycling / reprocessing capability of the glass-like polymer obtained by curing cardanol benzoxazine monomer.
[0147] - Fig.10 Shown is the evolution of the adhesive strength of the glass-like polymer of Example 2 used for bonding two steel blocks as a function of the number of fracture cycles.
[0148] - Fig.11 The synthesis of benzoxazine monomers from 3-pentadecylphenol as a phenolic derivative is shown.
[0149] - Fig.12 The NMR spectrum of 3-pentadecylphenolbenzoxazine monomer is shown.
[0150] - Fig.13 The DSC curve of 3-pentadecylphenol benzoxazine monomer is shown.
[0151] - Fig.14 The synthesis of benzoxazine monomers from phloric acid as a phenolic derivative is shown.
[0152] - Fig.15 The synthesis of benzoxazine monomers from eugenol as a phenolic derivative is shown. Example
[0153] Example 1: Synthesis of benzoic acid from cardanol as a phenolic derivative Nausea Oxazine monomer
[0154] Synthesis of disulfide-containing benzoxazine monomers using a mixture of cardanol (CAR), 4-aminophenyl disulfide (4apds), and paraformaldehyde (PFA) reactants ( Figure 1 ).
[0155] At room temperature, cardanol (5.97 g, 2 eq, 0.02 mol), 4-apds (2.48 g, 1 eq, 0.01 mol), and paraformaldehyde (1.20 g, 4 eq, 0.04 mol) were added to a 100 ml round bottom flask. The flask was heated at 70 ° C for 7 h using an oil bath, and the reaction medium was stirred using a magnetic stirrer. The reaction product was a yellow wax and was used for the elaboration of a glass-like polymer material without further purification.
[0156] Figure 3 It shows that Figure 1 NMR spectra (AVANCE III HD Bruker spectrometer) of cardanol derivative benzoxazine monomers with various n values shown in FIG.
[0157] Figure 4FTIR spectra (Bruker TENSOR 27) of cardanol derivative benzoxazine monomers with various n values are shown.
[0158] DSC results ( Figure 5 ) was obtained using an instrument (Netzsch DSC 204F1 Phoenix instrument) at 10°C / min in an inert atmosphere. The DSC curve shows an exothermic peak starting at a temperature of 130°C, with a maximum at 194°C, corresponding to the ring opening of the benzoxazine moiety upon heating.
[0159] Figure 6 The rheogram of the cardanol derivative benzoxazine monomer is shown in . The rheogram was performed under the following conditions: 1 Hz, linear amplitude 1 to 0.1%; 25 mm plate. The test was performed as follows: following a heating ramp from 100°C to 170°C at 10°C / min, followed by isothermal measurement at 170°C.
[0160] This test shows the evolution of the complex viscosity as a function of time. The monomer first softens (evidenced by a decrease in its complex viscosity reaching values of 100 mPa.s), which means that it can be easily processed by typical processing tools (such as injection machines, etc.).
[0161] After 15 minutes, the complex viscosity increased to 3.10 due to the benzoxazine ring opening and the first step of the reaction. 4 mPa.s. After 50 minutes, a second gelation was observed as the cross-linking process was being achieved.
[0162] Example 2: By making the cardanol derivative benzoic acid Nausea Synthesis of glass-like polymers obtained by curing oxazine monomers
[0163] In a Teflon mold, the benzoxazine monomer obtained in Example 1 was polymerized at 170° C. for 1 hour, and then post-cured at 190° C. for 30 minutes to obtain a glass-like polymer material of a cardanol derivative polybenzoxazine ( Figure 2 ).
[0164] The sample was immersed in DMF, toluene, and water to measure the swelling ability of the sample. In toluene and DMF, the sample swelled by 430% and 300%, respectively. In water, the sample did not swell.
[0165] The Tg of the material (defined as the maximum value of the loss modulus determined by rheological measurements) is 50°C.
[0166] Figure 7The evolution of the relaxation modulus of the glassy polymer of the cardanol derivative benzoxazine at different temperatures is shown as evidence of glassy polymer behavior. The decrease in the relaxation modulus represents a change in the shape of the sample. At 80°C, it takes 89 seconds for the material to lose 50% of its modulus. At 120°C, it takes 11 seconds. The relaxation temperature of the material is contained between 50 and 150°C.
[0167] The evolution of relaxation time Figure 8 The relaxation time is reported as a function of 1000 / T, with the relaxation time defined as the time required for the material to relax 50% of its initial modulus at a determined temperature. The evolution of ln(t*) as a function of 1000 / T is linear and follows the Arrhenius rule, which is evidence of an associative behavior of a glassy polymer. The activation energy of the material can be calculated from the slope of the trend line and is 65 kJ / mol.
[0168] The reprocessing temperature of the material is between 80°C and 120°C.
[0169] Fig. 9 An example of a glass-like polymer in Example 2 is shown, which has been subjected to twisting at 80° C., followed by a grinding step, and a reshaping and reprocessing step.
[0170] Fig.10 The evolution of the adhesive strength of the glass-like polymer of Example 2 used to bond two steel blocks is shown. For the purpose of clarity of the test, the scheme is reported on the figure. After each tensile test that resulted in the fracture of the assembly, the two blocks were reassembled together by heating the two blocks and the glass-like polymer of Example 2 at 120°C for 10 minutes under a pressure of 1 bar. Initially, the adhesive strength was measured to be equal to 1.08 MPa, without showing any significant decrease after 3 fracture / healing steps. After this third fracture, the assembly was rebonded by heating at 120°C for 2 minutes and pressing at 8 bar. After the fracture, the assembly was reshaped and retested 3 times, showing the ability to rebond. At the end of the 6th cycle, the glass-like polymer could be disassembled from the cube by heating at 120°C for 5 minutes and by pulling apart the steel cube. After the glass-like polymer has cooled, the glass-like polymer can still be used to bond the metal cube.
[0171] Example 3: Synthesis of benzoxazine monomers from 3-pentadecylphenol as a phenolic derivative
[0172] The synthesis of disulfide-containing benzoxazine monomers was carried out using a mixture of 3-pentadecylphenol (3-PDP), 4-aminophenyl disulfide (4apds) and paraformaldehyde (PFA) reactants ( Fig.11 ).
[0173] At room temperature, 3-pentadecylphenol (6.09 g, 2 eq, 0.02 mol), 4-apds (2.48 g, 1 eq, 0.01 mol), and paraformaldehyde (1.20 g, 4 eq, 0.04 mol) were added to a 100 ml round bottom flask. The flask was heated at 85 ° C for 7 h using an oil bath, and the reaction medium was stirred with a magnetic stirrer. The reaction product was a yellow wax and was used for the refinement of a glass-like polymer material without further purification.
[0174] Fig.12 The NMR spectrum (AVANCE III HD Bruker spectrometer) of the 3-pentadecylphenol derivative benzoxazine monomer is shown.
[0175] DSC results ( Fig.13 ) was obtained using an instrument (Netzsch DSC 204F1 Phoenix instrument) at 10°C / min in an inert atmosphere. The DSC curve shows a broad exothermic peak starting at a temperature of 170°C, with a maximum at 232°C, corresponding to the ring opening of the benzoxazine moiety upon heating.
[0176] The curing of 3-pentadecylphenol derivative benzoxazine monomers was monitored by rheological measurements.
[0177] The rheograms were carried out under the following conditions: 1 Hz, linear amplitude 1 to 0.1%; 25 mm plate. The test was carried out following a heating ramp from 100°C to 200°C at 10°C / min followed by isothermal measurement at 200°C.
[0178] The complex viscosity is recorded as a function of time. The monomer first softens (evidenced by a decrease in its complex viscosity reaching a value of 100 mPa.s), which means that it can be easily processed by typical processing tools (such as injection machines etc.).
[0179] After 200 minutes, the complex viscosity increased to 10 due to the ring opening of the benzoxazine. 4 mPa.s.
[0180] Example 4: Synthesis of glass-like polymer obtained by curing 3-pentadecylphenol benzoxazine monomer
[0181] In a Teflon mold, the benzoxazine monomer obtained in Example 3 was polymerized at 200° C. for 2 h, and then post-cured at 220° C. for 2 h to obtain a glass-like polymer material of 3-pentadecylphenol polybenzoxazine.
[0182] The sample was immersed in DMF, toluene, and water to measure the swelling ability of the sample. In toluene and DMF, the sample swelled 800% and 600%, respectively. In water, the sample did not swell.
[0183] The Tg of the material (defined as the maximum value of the loss modulus determined by rheological measurements) was 18°C.
[0184] The evolution of the relaxation modulus of the glassy polymer of 3-pentadecylphenolbenzoxazine was followed by rheology at different temperatures as evidence of glassy polymer behavior. The decrease in relaxation modulus represents a change in the shape of the material. At 80°C, it takes 42 seconds for the material to lose 50% of its modulus. At 120°C, it takes 6 seconds. The relaxation temperature of the material is comprised between 40 and 150°C. The reprocessing temperature of the material is between 40°C and 120°C.
[0185] Example 5: Synthesis of benzoxazine monomers from phloric acid as phenolic derivatives
[0186] The synthesis of disulfide-containing benzoxazine monomers was carried out using a mixture of phloric acid (PA), 4-aminophenyl disulfide (4apds), and paraformaldehyde (PFA) as reactants. Fig.14 ).
[0187] At room temperature, phlorothiolane (3.32 g, 2 eq, 0.02 mol), 4-apds (2.48 g, 1 eq, 0.01 mol) and paraformaldehyde (1.20 g, 4 eq, 0.04 mol) were added to a 100 ml round bottom flask. The flask was heated at 85 ° C for 7 h using an oil bath, and the reaction medium was stirred with a magnetic stirrer. The reaction product was a brown wax and was used for the refinement of a glass-like polymer material without further purification.
[0188] 1 H NMR (CDCl 3 ): [a]2.5-2.6ppm; [b]2.8-2.9ppm; [4]4.5ppm; [5]5.3ppm; [1,2]6.5-6.7ppm; [d ]6.75ppm; [6,7]6.8-6.9ppm; [3]7.0ppm; [c]7.15ppm; [8,9]7.3ppm; [e]11.5ppm.
[0189] DSC results were obtained using an instrument (Netzsch DSC 204F1 Phoenix instrument) at 10°C / min in an inert atmosphere. The DSC curve shows a broad exothermic peak starting at a temperature of 130°C with a maximum at 176°C, corresponding to the ring opening of the benzoxazine moiety upon heating.
[0190] The curing of phloroglucinol benzoxazine monomers was monitored by rheological measurements.
[0191] The rheograms were carried out under the following conditions: 1 Hz, linear amplitude 1 to 0.1%; 25 mm plate. The test was carried out following a heating ramp from 100°C to 170°C at 10°C / min followed by isothermal measurement at 170°C.
[0192] The complex viscosity is recorded as a function of time. The monomer softens first (as evidenced by a decrease in its complex viscosity of up to 100 mPa.s), which means that it can be easily processed by typical processing tools (such as injection machines, etc.). After 10 minutes, the complex viscosity increases to 4.10 due to the ring opening of the benzoxazine. 4 mPa.s.
[0193] Example 6: Synthesis of glass-like polymers obtained by curing benzoxazine phlorate monomers
[0194] In a Teflon mold, the benzoxazine monomer obtained in Example 5 was polymerized at 170° C. for 2 hours, and then post-cured at 190° C. for 30 minutes to obtain a glass-like polymer material of phloroglucinol polybenzoxazine.
[0195] The evolution of the relaxation modulus of the glassy polymer of benzoxazine phlorothiolane was followed by rheology at different temperatures as evidence of glassy polymer behavior. The decrease in relaxation modulus represents a change in the shape of the material. At 150°C, it takes 95 minutes for the material to lose 50% of its modulus. At 120°C, it takes 6 seconds. The relaxation temperature of the material is comprised between 120 and 190°C.
[0196] The reprocessing temperature of the material is between 80°C and 120°C.
[0197] Example 7: Synthesis of benzoxazine monomers from eugenol as phenolic derivatives
[0198] Eugenol (EUG), 4-aminophenyl disulfide (4apds), and paraformaldehyde (PFA) reactants ( Fig.15 ) was used to synthesize a disulfide-containing benzoxazine monomer.
[0199] Eugenol (3.28 g, 2 eq, 0.02 mol), 4-apds (2.48 g, 1 eq, 0.01 mol), and paraformaldehyde (1.20 g, 4 eq, 0.04 mol) were added to a 100 ml round bottom flask at room temperature. The flask was heated at 85 ° C for 7 h using an oil bath, and the reaction medium was stirred using a magnetic stirrer. The reaction product was a brown wax and was used for the refinement of a glass-like polymer material without further purification.
[0200] 1 H NMR (CDCl 3): [c]3.4ppm; [f]3.8-3.9; [4]4.5ppm; [a]5.1-5.2ppm; [5]5.3ppm; [b]5.9ppm; [ d,e]6.4-6.6ppm; [1,2]6.5-6.7ppm; [6,7]6.8-6.9ppm; [3]7.0ppm; [8,9]7.3ppm.
[0201] DSC results were obtained using an instrument (Netzsch DSC 204F1 Phoenix instrument) at 10°C / min in an inert atmosphere. The DSC curve shows a broad exothermic peak starting at a temperature of 125°C with a maximum at 200°C corresponding to the ring opening of the benzoxazine moiety upon heating.
[0202] The curing of eugenol benzoxazine monomer was monitored by rheological measurements.
[0203] The rheograms were carried out under the following conditions: 1 Hz, linear amplitude 1 to 0.1%; 25 mm plate. The test was carried out following a heating ramp from 100°C to 170°C at 10°C / min followed by isothermal measurement at 170°C.
[0204] The complex viscosity is recorded as a function of time. The monomer first softens (evidenced by a decrease in its complex viscosity reaching a value of 100 mPa.s), which means that it can be easily processed by typical processing tools (such as injection machines etc.).
[0205] After 45 minutes, the complex viscosity increased to 2.10 due to the ring opening of the benzoxazine. 4 mPa.s.
[0206] Example 8: Synthesis of glass-like polymers obtained by curing eugenol benzoxazine monomers
[0207] In a Teflon mold, the benzoxazine monomer obtained in Example 7 was polymerized at 170° C. for 2 hours, and then post-cured at 190° C. for 30 minutes to obtain a glass-like polymer material of a eugenol derivative polybenzoxazine.
[0208] The evolution of the relaxation modulus of the glassy polymer of benzoxazine phlorothiolane was followed by rheology at different temperatures as evidence of glassy polymer behavior. The decrease in relaxation modulus represents a change in the shape of the material. At 120°C, it takes 7 minutes for the material to lose 50% of its modulus. The relaxation temperature of the material is comprised between 50 and 150°C.
[0209] The reprocessing temperature of the material is between 120°C and 180°C.
Claims
1. Disulfide-containing benzoxazine monomer of formula I Where R is: And the combination of R1, R2, R3, R4 substituents is selected from the following combinations: R1=OCH3, R2=R4=H, R3=C1-C 15 The alkyl group, R1=OCH3, R2=R4=H, R3=(CH2) n COOH, wherein n=1-15, R1=OCH3, R2=R4=H, R3=(CH2) n CH=CH2, where n=1-15, R1=R2=R4=H,R3=(CH2) n COOH, wherein n=1-15, At least one of R1, R2, R3 and R4 is C1-C 15 aliphatic alkyl group, the rest are H, R1=R3=R4=H, and R3=R4=H, R1=COOH, and R1=H, R2=OH, R3=H, and R1=H, R3=OH, R4=H, and R1=CH3, R2=OH, R3=H, R3=R4=H, R1=OH, and R2=R3=R4=H, and R1=(CH2) n CH=CH2, where n=1-15, R1=R3=R4=H, and R2=(CH2) n CH=CH2, where n=1-15, and R1=R2=R4=H, and R3=(CH2) n CH=CH2, wherein n=1-15; or a mixture thereof, The combination of R1', R2', R3', and R4' substituents is as defined for the combination of R1, R2, R3, and R4 substituents, and is independent thereof.
2. The disulfide-containing benzoxazine monomer according to claim 1, wherein the combination of R1, R2, R3, and R4 substituents is selected from the following combinations: R1=R3=R4=H, and 3. A process for synthesizing a disulfide-containing benzoxazine monomer of formula (I) as defined in claim 1, the process comprising the following steps consisting of: a) providing a mixture comprising: - aminodisulfide compounds of formula (III): H2N-R-NH2, wherein R is as defined for the monomer of formula (I), - aldehyde derivatives, the aldehyde derivatives are selected from formaldehyde, and paraformaldehyde, or a mixture thereof; and - Phenol derivatives of formula (IV) and (V) wherein the combination of R1, R2, R3, R4 and R1', R2', R3', R4' substituents are independent, as defined in claim 1 or 2, and wherein R5 and R5' are independently H, b) stirring the mixture at a temperature of 50° C. to 130° C. for 1 to 48 hours to obtain the monomer of formula (I); The stoichiometric ratios of aminodisulfide compound: aldehyde derivative: phenol derivative are 1:4:x1+x2, wherein x1+x2=2, and 0 <x1;x2<2。 4. The process according to claim 3, wherein the temperature of the mixture is from 60°C to 130°C and the reaction duration is from 1 h to 48 h.
5. The process according to claim 3, wherein the process is carried out without using any solvent, the reaction temperature is in the range of 60°C to 120°C, and the reaction duration is 1h to 24h.
6. The process according to claim 3, wherein the process is carried out using a solvent, the reaction temperature is in the range of 70°C to 130°C, and the reaction duration is 5h to 24h.
7. A process for preparing a glass-like polymer of a polybenzoxazine derivative, the process comprising a step of polymerizing the benzoxazine monomer of claim 1 or 2 or the benzoxazine monomer obtained by the process of any one of claims 3 to 6 at a temperature in the range of 100° C. to 250° C. for 1 h to 24 h to obtain a glass-like polymer of a polybenzoxazine derivative.
8. A process according to claim 7, wherein the curing temperature is from 170°C to 190°C, providing a curing duration of from 1 h to 3 h.
9. A glass-like polymer of a polybenzoxazine derivative obtained by the process according to claim 7 or 8, exhibiting at least one of the following properties: (i) a Tg value of 0°C to 250°C; and (ii) The relaxation temperature is between 0°C and 250°C, above the Tg value.
10. The glass-like polymer according to claim 9, wherein the glass-like polymer exhibits at least one of the following properties selected from the group consisting of: - a relaxation time of 0.1 s to 2 h, wherein the relaxation time is defined as the time required for a glass-like polymer to relax by 50% at a predetermined temperature after stress is applied; - an activation energy associated with the relaxation time of 10 kJ / mol to 300 kJ / mol; and - Reprocessing temperature is 50℃ to 200℃.
11. A glass-like polymer according to claim 9 or 10, wherein the glass-like polymer exhibits the following characteristics: it behaves as a thermoset, and / or exhibits insolubility in aromatic solvents, and has a swelling property to the extent of 0 to 500% of its initial weight.
12. The glass-like polymer according to claim 9 or 10, wherein the glass-like polymer constitutes an intermediate layer between at least two substrates.
13. Composition A, comprising: a) a benzoxazine derivative of formula (I) as defined in claim 1, and b) at least one or more additional compounds of the organic molecular type, which may or may not contain a benzoxazine moiety.
14. Composition B, comprising: a) a benzoxazine derivative of formula (I) as defined in claim 1, and b) Materials selected from fillers, fibers, pigments, and plasticizers.
15. Composition B, comprising: a) a benzoxazine derivative of formula (I) as defined in claim 1, and b) Materials selected from dyes.
16. Use of a glass-like polymer according to any one of claims 9 to 12 or obtained by a process according to claim 7 or 8 as a reversible adhesive, sealant, coating, or encapsulation system for a substrate selected from metals, polymers, glass, and ceramic materials.
Citation Information
Patent Citations
Photo-active benzoxazine resin and preparation method thereof
CN108997548A